2014
DOI: 10.1021/am507108u
|View full text |Cite
|
Sign up to set email alerts
|

CH3NH3PbI3-Based Planar Solar Cells with Magnetron-Sputtered Nickel Oxide

Abstract: Herein we report an investigation of a CH3NH3PbI3 planar solar cell, showing significant power conversion efficiency (PCE) improvement from 4.88% to 6.13% by introducing a homogeneous and uniform NiO blocking interlayer fabricated with the reactive magnetron sputtering method. The sputtered NiO layer exhibits enhanced crystallization, high transmittance, and uniform surface morphology as well as a preferred in-plane orientation of the (200) plane. The PCE of the sputtered-NiO-based perovskite p-i-n planar sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
167
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 35 publications
5
167
1
3
Order By: Relevance
“…The NiO x ‐based PSCs exhibit a relatively low PCE of 14.7%, along with a V oc of 1041 mV, a FF of 0.7, and a J sc of 20.3 mA cm −2 . Despite this, it is worthwhile noting that our sputtered NiO x ‐based solar cells still perform better than the previously reported results, the highest efficiency of which is only 11.6% 31, 32. We note that the previous results are based on the NiO x HTL sputtered using a high oxygen partial pressure.…”
contrasting
confidence: 74%
“…The NiO x ‐based PSCs exhibit a relatively low PCE of 14.7%, along with a V oc of 1041 mV, a FF of 0.7, and a J sc of 20.3 mA cm −2 . Despite this, it is worthwhile noting that our sputtered NiO x ‐based solar cells still perform better than the previously reported results, the highest efficiency of which is only 11.6% 31, 32. We note that the previous results are based on the NiO x HTL sputtered using a high oxygen partial pressure.…”
contrasting
confidence: 74%
“…5. 3,8,21 Based on the measurements taken by the surface analyzer, the work function of the sputtered NiO x was estimated to be ca. 5.5 eV.…”
Section: ¹1mentioning
confidence: 99%
“…15 Recently, several hole transport materials (HTM) have also been introduced into the perovskite solar cells in place of PEDOT:PSS to obtain probable device application or efficient devices. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] The typical requirements for HTMs of perovskite solar cells are as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 PCBM (phenyl-C 61 -butyric acid methyl ester) is commonly used as the electron transport layer in the p-i-n structure, but this material is often combined with other layers, such as bathocuproine (BCP), to block holes and improve the power conversion efficiency. 15,17,18 Incorporating additional layers into the solar cell's device structure leads to increased complexity in processing, and therefore it is desirable to replace the electron transport layer to simplify the overall device structure. Recently, Yin et al showed NiO x -based solar cells with only PCBM as the electron transport layer (ETL), reaching a power conversion efficiency (PCE) of 15.7%.…”
Section: 1% © 2017 Author(s) All Article Content Except Where Othmentioning
confidence: 99%